Work Discipline and Social Capital in Influence Workload and Employee Performance Abstract AI Regional Planning and Development Agency of North Kalimantan Province - Agretha, Agretha; Hidayat, Zainur; Sriekaningsih, Ana (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: to explain the Work Discipline and Social Capital in Influence Workload and Employee Performance Abstract AI Regional Planning and Development Agency Desain / Metodology / Approach: Substructural Path Equation Analysis I, The Influence of Work Discipline on Workload Finding: The research design uses an explanatory design using mediating variables, namely variables that mediate the relationship between the explanatory variable and the response or dependent variable. Practical Implication: The research aims to determine work discipline and social capital in influencing the workload and performance of employees of the Regional Planning and Development Agency of North Kalimantan Province. Originality / Value: This Paper is Original Paper Type: Research